Providing safety in a rush: How did shadow banks respond to a $1 trillion shock? - Gissler, Stefan; Macchiavelli, Marco; Narajabad, Borghan (Journal of Financial Intermediation, 2025)
During a flight to liquidity, investors demand large amounts of governmentbacked safe assets in a rush. The sluggish reaction of the public supply of safe assets opens up a role for government-sponsored shadow banks. We exploit exogenous changes in both demand and supply of safe assets from the 2014 money fund reform and the 2015 debt limit. We find that shadow banks act as a substitute as well as a complement to public supply during a flight to liquidity. Our findings carry over to the dash for cash at the onset of the Covid-19 pandemic. JEL classification: G23, G28, E41.